Pengaruh Kelompok Usaha Bersama (KUBe) Terhadap Kemampuan Berwirausaha Keluarga Sangat Miskin Di Kabupaten Wonogiri - Devina Melinawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
This study aims to determine the effect of the Joint Business Group Program (KUBe) on the entrepreneurial ability of Very Poor Families in Wonogiri Regency. This research method uses quantitative methods with a cross sectional survey approach. The data analysis technique used in this study is regression analysis. The results showed that the Joint Business Group (KUBe) program had a positive influence on entrepreneurial ability.